2(-4z-5)+16=-2(4z-3)+0

Simple and best practice solution for 2(-4z-5)+16=-2(4z-3)+0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(-4z-5)+16=-2(4z-3)+0 equation:


Simplifying
2(-4z + -5) + 16 = -2(4z + -3) + 0

Reorder the terms:
2(-5 + -4z) + 16 = -2(4z + -3) + 0
(-5 * 2 + -4z * 2) + 16 = -2(4z + -3) + 0
(-10 + -8z) + 16 = -2(4z + -3) + 0

Reorder the terms:
-10 + 16 + -8z = -2(4z + -3) + 0

Combine like terms: -10 + 16 = 6
6 + -8z = -2(4z + -3) + 0

Reorder the terms:
6 + -8z = -2(-3 + 4z) + 0
6 + -8z = (-3 * -2 + 4z * -2) + 0
6 + -8z = (6 + -8z) + 0

Reorder the terms:
6 + -8z = 6 + 0 + -8z

Combine like terms: 6 + 0 = 6
6 + -8z = 6 + -8z

Add '-6' to each side of the equation.
6 + -6 + -8z = 6 + -6 + -8z

Combine like terms: 6 + -6 = 0
0 + -8z = 6 + -6 + -8z
-8z = 6 + -6 + -8z

Combine like terms: 6 + -6 = 0
-8z = 0 + -8z
-8z = -8z

Add '8z' to each side of the equation.
-8z + 8z = -8z + 8z

Combine like terms: -8z + 8z = 0
0 = -8z + 8z

Combine like terms: -8z + 8z = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 17x-4(x-2)=-5 | | 5x-2+10=4x+8+10 | | 3.50=1.90+c | | -24x-31-8x+40x-9=-5x+8+15x | | Inx=-In(x+1) | | 2(3x-1)=x^2+7x-8 | | 26+4y-8=14y-10-3y | | 40*x+(12.5x*1.5)= | | 3.5h=14 | | 2.25(x-42)=x+3.28 | | 2=y/3.2 | | W/4-2=12x^4 | | 11+-12=-25 | | -4(x+3)-3=6(x-6) | | X^2-5x-5=-5 | | -2h+9h=16 | | 23+g=30 | | 10x+3=8x+18 | | 4x-6+5=2+5 | | 5v-17=78 | | 2(-2)+y=72 | | 2x=(x+4) | | (22-x)/x=-1 | | f(x)=-(x+3)*2+1 | | 3[x-4]=-4x+37 | | Y-1/6=-4/5 | | W/4-2=12x4 | | -3y+1(-9y-3)=-8+2(6-y) | | 11=3x+-25 | | 4(x+4)+2x=52 | | 30+5(x-3)=4(x+2)+3x | | 180+180(.1667)= |

Equations solver categories